PENEMUAN HUKUM (RECHTSVINDING) HAKIM DALAM PERKARA PERDATA SEBAGAI ASPEK MENGISI KEKOSONGAN HUKUM - Markus Suryoutomo; Mahmuda Pancawisma Febriharini (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
Interpreting a legal rule is an effort to find the meaning of the legal rule, which means distilling or drawing out and displaying it to the surface of the rule of law or the meaning of law that is contained or hidden in the legal rule concerned. Regarding the method or method to find the rule of law, in legal studies various interpretation methods have been developed, including grammatical, historical, systematical, teleological and sociological methods. Regarding the methods there is no stipulation on hierarchical order. Yet it is not impossible that these methods produce different interpretations. However, hermeneutic studies show that all methods need to be involved proportionally in relation to one another whenever interpreting a rule of law.